Biphenyl derivatives from the twigs of Garcinia bracteata and their biological activities. (March 2015) - Li, Yinke; Wang, Zhengyin; Wu, Xianxue; Yang, Yuchun; Qin, Ying; Xia, Congfang; Meng, Yanlin; Li, Ming; Gao, Xue-Mei; Hu, Qiufen
Graphical abstract: Highlights: Three new (1 –3 ) and five known (4 –8 ) biphenyl derivatives were isolated form Garcinia bracteata. 1 –8 were evaluated for their anti-TMV activities, and3 showed high activity with inhibition rate of 28.4%. 1 –3, 6, 8 were tested for their cytotoxicities. 3 showed high cytotoxicities against A549 and PC3 cell with IC50 values of 3.6 and 2.7 μM. Abstract: Three new biphenyl derivatives, bractebiphenyls A–C (1 –3 ), along with five known biphenyl derivatives (4 –8 ) were isolated from the acetone extract of the twigs of Garcinia bracteata . Their structures were elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. The anti-tobacco mosaic virus (anti-TMV) activities of1 –8 were evaluated. Compound3 showed high anti-TMV activities with inhibition rates of 28.4%, which is close to that of Ningnanmycin (30.2%). Compounds1 –3, 6 and8 were also tested for their cytotoxicities against five human tumor cell lines (NB4, A549, SHSY5Y, PC3, and MCF7), and3 showed high cytotoxicities against A549 and PC3 cell with IC50 values of 3.6 and 2.7 μM, respectively.